The Integrity of Integrity Programs: Toward a Normative Framework. (4th March 2021) - Hoekstra, Alain; Kaptein, Muel
Abstract : Most of the norms developed for integrity programs are grounded in positivist arguments focused on effectiveness. The norms developed in this article are grounded in normative arguments that are directly deduced from the concept of integrity itself. The four norms are intentional wholeness; organizational wholeness; societal wholeness; and processual wholeness. These norms are operationalized into subnorms and indicators, resulting in a normative framework that helps to assess and advance the integrity of integrity programs.